Efisiensi Biaya Dan Penjadwalan Proyek Rehabilitasi Puskesmas Rawat Inap Pesanggrahan, Kutorejo, Mojokerto - Isnaini, Nurdiana Fitri (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2019)
Control is one of the functions of project management which aims to ensure that work can achieve its goals without many deviations. The relationship between direct costs and indirect costs to time has a tendency to be the opposite. If the project implementation time is accelerated it will result in an increase in direct costs but in the indirect costs there will be a decrease. The results of the analysis using the cost control method and the integrated schedule (earned value concept) for the implementation of the Pesanggrahan Inpatient Puskesmas Rehabilitation Project in Kutorejo Subdistrict, Mojokerto Regency on the project implementation performance in terms of cost shows that the implementation of the project has benefited, this is indicated by the CV indicator (cost variant ) has a positive value of Rp. 60,475,147 or the performance index value (CPI) = 1.07> 1. While the aspect of the project implementation schedule is experiencing delays as indicated by the SV indicator (schedule variance) is negative Rp. -102,477,511 Or SPI schedule performance index = 0.90 <1. Project performance when reporting is running well, profits will be obtained because the funds spent are still under the planned budget. A positive ETC value of Rp. 9,773,374 While from the aspect of schedule, the implementation experienced a slight delay from the specified schedule, it can be seen from the August EAS of 90 days, so that the September EAS was above 90 days.